ANALISIS STRATEGI PEMASARAN DALAM MENINGKATKAN PENJUALAN PADA TOKO BUAH NUR BUAH BLITAR - Frestina Maya Safitri; Rifda Izzatun Nada; Ika Nurfitriani (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2026)
This study aims to determine marketing strategies for fresh fruit businesses located in Kanigoro, Blitar, East Java, and to serve as a reference for decision-making regarding marketing strategies for several fruit stores in Blitar in order to increase sales in the future. The marketing strategy was formulated through a Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis, which was then outlined using the Internal Factor Analysis Strategic (IFAS) and External Factor Analysis Strategic (EFAS) methods. The results of the IFAS and EFAS analyses were subsequently mapped into a SWOT diagram to determine the appropriate strategy based on the data analysis. The results of the SWOT diagram analysis indicate that the business is positioned in Quadrant I, suggesting an aggressive strategy by utilizing external opportunities to maximize internal strengths.